Os compostos no crioulo português da Guiné-Bissau - Couto, Hildo Honório do (2011)
ABSTRACT: Compounding is one of the most widespread morphological processes in languages around the world. In Guinea-Bissau Creole it is very frequent, including reduplication, which will not be dealt with here. In this creole, expressions like "kau di sinta" (where to sit down) are difficult to be classified as a single item of the vocabulary or as a phrase. Our thesis is that departing from semantics, not from syntax, we have a surer way of deciding whether we have a word or a phrase. In other words, as was the case with the "Wörter und Sachen" movement in dialectology, expressions like this designate a single object, namely bench. Knowing this, we can go to syntax, where we see that they can be preceded by determiners, be subject of sentences and so on, like any substantive.